Parkinson's disease due to the R1441G mutation in Dardarin: A founder effect in the basques - Simón-Sánchez, Javier; Martí-Massó, José-Félix; Sánchez-Mut, José Vicente; Paisán-Ruiz, Coro; Martínez-Gil, Angel; Ruiz-Martínez, Javier; Sáenz, Amets; Singleton, Andrew B.; López de Munain, Adolfo; Pérez-Tur, Jordi (Movement disorders, 2006)
The recent discovery of mutations in Dardarin (LRRK2) have been related to the appearance of Parkinson's disease in several families. Notably, one single mutation in this gene (R1441G) not only appeared in familial, but also in apparently sporadic Parkinson disease (PD) patients of Basque descent. A clinical population was ascertained, and subjects were classified into Basque and non‐Basque descent according to their known ancestry. The R1441G mutation was assayed using an allele‐specific polymerase chain reaction, and several single nucleotide polymorphisms surrounding this mutation were analyzed by direct sequencing. In addition to 22 members of the original Basque families where R1441G was identified, we observed 17 carriers of the mutation who were apparently related through a common ancestor. From a clinical perspective, the disease observed in mutation carriers is indistinguishable from that in noncarriers. The R1441G mutation causes a form of Parkinson's disease that is equivalent to that observed in idiopathic Parkinson's disease. This mutation appears in 16.4% and 4.0% of familial and sporadic PD in this Basque population, respectively. © 2006 Movement Disorder Society